Use of Verbal Autopsy as a Proxy to Determine the Possible Cause of Neonatal Deaths - Baghel, B; Bansal, AK (Journal of Nepal Paediatric Society, 2011)
Introduction: Information on causes of death is extremely important for policy making, planning, monitoring, field research, future management statergies and epidemic awareness. The best method of finding the cause of death is by post mortem examination but since this is difficult, post death analysis by verbal autopsy is a good method to determine the same. Objective: To asses the role of verbal autopsy method in the investigation of neonatal death and to determine the probable, causes of neonatal death. Materials and Methods: A pre-tested questionnaire in Hindi was administered to 50 mothers and/or next of kin or other care givers of the deceased residing in villages around 200 Kms. of Bhopal and in urban slums of Municipal Corporation, Bhopal. Results: 84 % of the total death occurred with in seven days of birth, 88 % of death occurred in villages where health facilities were available. As per verbal autopsy 36 % and 20 % of the infants died because of Birth asphyxia and Respiratory Distress Syndrome respectively and further 2%, 4% and 6% because of neonatal tetanus, hypothermia and other causes respectively. Conclusion: Verbal autopsy could be one of the possible cost effective and a reliable tool for determining the causes of neonatal deaths at present. Key words: Verbal Autopsy; Neonatal death; Reliable respondents and category of villages. DOI: 10.3126/jnps.v31i1.2942 J Nep Paedtr Soc 2010;31(1):44-48